PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN MOTIVASI SISWA DI KELAS VII SMPN 30 MUARO JAMBI - Hapizoh, Atika; Jufrida, Jufrida; Darmaji, Darmaji (EduFisika: Jurnal Pendidikan Fisika, 2020)
This research was motivated by low of motivation to learn physics at SMPN 30 Muaro Jambi. By using the Contextual Teaching and Learning (CTL) learning model, it is expected that students will more easily to understand and receive knowledge effectively and efficiently. So, it can increase student learning motivation, because the temperature material and its changes contain a description of the material that is conceptual and quantitative, so in presenting this material a learning model is needed to encourage student learning motivation. From the results, it can be seen that there is an increase in learning motivation experienced by students from the first cycle 59.74% to 72.18% in cycle II and 82.61% in cycle III. Thus it can be concluded that the application of the Contextual Teaching and Learning (CTL) learning model can increase student motivation in class VII B SMPN 30 Muaro Jambi.